Motherboard maker ECS diversifies into consumer electronics. IN InfoTech - Gomez, Raquel P. (Philippine Daily Inquirer)
In order for us to thrive in the new field like the smartphones and tablets, we need more providers of OS and chip solution to power the devices. And this means more choices for the consumers.